THE SEMANTIC REPRESENTATION OF THE CONCEPT “BEAUTY” IN UZBEK AND ENGLISH LANGUAGE CULTURE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
Beauty is one of the most important aesthetic concepts in human cognition and cultural consciousness. The present study purpose to explore the semantic representation of the concept “beauty” in Uzbek and English language cultures from a cognitive and cultural linguistic perspective. The research is conducted within a comparative framework. The methods applied in this study include conceptual analysis, semantic interpretation, and comparative analysis of metaphorical and evaluative language units. The theoretical basis of the research relies on Conceptual Metaphor Theory, semiotics, and cultural semantics. The results of the study show that while beauty is a universal concept, its linguistic realization differs considerably across cultures.In Uzbek culture, the notion of beauty is largely associated with inner virtue, humility, and a connection with nature, while in English culture, more importance is given to physical appearance, personal uniqueness, and aesthetic appreciation. The study finds that cultural values and the national perspective significantly effect how the concept of “beauty” is semantically constructed in both languages.